1343. Body fat and metabolic complications in youth with perinatally-acquired HIV. (15th December 2022) - Dirajlal-Fargo, Sahera; Jacobson, Denise L; Yu, Wendy; Mirza, Ayesha; Geffner, Mitchell E; McComsey, Grace A; Jao, Jennifer
Abstract: Background: The role of obesity on long-term metabolic complications remains poorly understood in youth living with perinatally-acquired HIV (YPHIV). Methods: The PHACS Adolescent Master Protocol (AMP) study enrolled YPHIV from 2007-2009 across 15 U.S. sites, including Puerto Rico. We included YPHIV aged 7-19 yr with body composition data assessed by whole-body dual energy x-ray absorptiometry (DXA) at baseline and 2 years later. Metabolic outcomes included homeostatic assessment of insulin resistance (HOMA-IR) and non-high-density lipoprotein cholesterol (non-HDL-C). We fit linear regression models using generalized estimating equations to assess the association of % change in body and trunk fat over 2 yr with metabolic outcomes at years 2 and 3, adjusted for potential confounders (age, race: Black vs. non-Black, Tanner stage, sex, family history, CD4, viral load, and ART). Results: 232 participants had a second DXA and either HOMA-IR or non-HDL-C measured at year 2. Participant characteristics at the first DXA were: median (Q1, Q3) age 12 yr (9, 14) 70% Black, CD4 count 714 cells/mm 3 ; 70% with HIV RNA < 400 copies/mL; 72% on protease inhibitor-, 25% on non-nucleoside reserve transcriptase inhibitor-, and 3% on integrase strand transfer inhibitor-based ART. The median % increase from baseline in total body and trunk fat percentage at 2 yr was 5.41% and 4.47%, respectively. The figure shows distributions of HOMA-IR and non-HDL-C. In both unadjusted and adjusted analyses (Table), for every 1% increase in total body fat percentage from baseline to 2 years, we observed a 0.002 (95%CI -0.0, 0.005) higher log10 HOMA-IR at year 3, which equals ∼ a 0.5% higher HOMA-IR. For every 1% increase in total body and trunk fat percentage over 2 years, non-HDL-C (mg/dL) was 0.19 (95%CI 0.03, 0.35) higher and 0.65 (95%CI 0.12, 1.19) higher, respectively, in unadjusted models. Results were similar but slightly attenuated when we additionally adjusted for confounders including ART. Figure: HOMA-IR and non-HDL cholesterol at baseline, year 2, and year 3 Table: Unadjusted and adjusted models assessing the association of percent change in body fat and trunk fat percentage with metabolic outcomes ¹Adjusted for age (years), sex (male vs female), race (Black vs non-Black), Tanner stage (2, 3, 4-5 vs 1), family history of diabetes or cardiovascular disease (yes, not known vs no), CD4 (≤350 vs >350 cells/mm³), and viral load (≥400 vs <400 copies/mL). ²Adjusted for age (years), sex (male vs female), race (Black vs non-Black), Tanner stage (2, 3, 4-5 vs 1), family history of diabetes or cardiovascular disease (yes, not known vs no), CD4 (≤350 vs >350 cells/mm³), viral load (≥400 vs <400 copies/mL), and ARV exposure (PI without NNRTI, NNRTI without PI vs other). Conclusion: Increases in adiposity over time may lead to downstream decreased insulin sensitivity and dyslipidemia in YPHIV. This is clinically significant, as even small increases in HOMA-IR have been associated with all-cause mortality in non-diabetic HIV-uninfected adults. Long-term follow-up is warranted. Disclosures: Mitchell E. Geffner, MD, Adrenas: Advisor/Consultant|Adrenas: Honoraria|Ascendis: Advisor/Consultant|Ascendis: Honoraria|Aventria: Honoraria|Eton: Advisor/Consultant|Eton: Honoraria|ICON Clinical Research, LLC/Aeterna Zentaris: Advisor/Consultant|ICON Clinical Research, LLC/Aeterna Zentaris: Honoraria|McGraw-Hill: Royalties|Neurocrine Biosciences: Grant/Research Support|Novo Nordisk: Grant/Research Support|Nutritional Growth Solutions Ltd: Advisor/Consultant|Nutritional Growth Solutions Ltd: Honoraria|Pfizer, Inc.: Advisor/Consultant|Pfizer, Inc.: Honoraria|Spruce Biosciences: Grant/Research Support|UpToDate: Royalties Grace A. McComsey, MD, Gilead, Merck, ViiV, Janssen, Theratechnologies: Advisor/Consultant.